Analisis Pengaruh Penerapan PTOS-M (Pelindo Terminal Operating System Multipurpose) Terhadap Kinerja Bongkar Muat Kayu Log di PT Pelindo Multi Terminal Branch Gresik - Dela Agussetiawati Alam; Romanda Annas Amrullah; Ita Masita; Elly Kusumawati (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
The smooth loading and unloading of logs at the port requires a reliable support system; therefore, PT. Pelindo Multi Terminal's Gresik Branch implemented PTOS-M (Pelindo Terminal Operating System Multipurpose) to improve log handling performance. This study aims to determine the effect of PTOS-M implementation on log loading and unloading performance at the company. A descriptive quantitative and causal-associative approach was used, applying simple linear regression analysis with SPSS 26 based on questionnaires, observations, and documentation involving 50 respondents. Descriptive results show PTOS-M implementation scored an average of 4.024, while log loading and unloading performance scored an average of 4.192. The regression coefficient (b = 0.292) indicates a positive relationship between the two variables. The R² value of 0.680 shows that PTOS-M implementation accounts for 68% of the variation in log handling performance, with the remaining 32% explained by other factors outside this study. The t-test produced a calculated t-value of 2.021 > t-table 2.011, with a significance level of 0.049 < 0.05, indicating that PTOS-M implementation has a positive and significant effect on log loading and unloading performance.